Bioactive Compounds of Acai (Euterpe oleracea) and the Effect of their Consumption on Oxidative Stress Markers - Guzmán, Romel; Aponte, Ricardo; Lares, Mary (Journal of Nutritional Therapeutics, 2021)
Açaí fruit (Euterpe oleracea Martius) is highly perishable, so it sought to apply conservation techniques that make its commercialization more bearable such as dehydration by the tray. This thermal technique that significantly inactivates harmful enzymes and microorganisms prolongs their shelf life but has the disadvantage that it decreases the proportion of bioactive components and its antioxidant power. The present work aims to estimate the content and antioxidant activity of the bioactive compounds of açaí powder supplied in hydroxypropyl methylcellulose (HPMC) vegetable capsules. For this purpose, total polyphenols were determined by the Folin-Ciocalteau test, total anthocyanin’s by the differential pH test, and the antioxidant capacity in vitro DPPH method (using Trolox and Vitamin C equivalent). Also, the effect of consumption of four daily capsules on a healthy population (10 people) between the ages of 33-65 years old evaluated through a 10-day intervention study in which the following biomarkers in blood assessed: glycemia, triglycerides, total cholesterol, HDL, LDL, and 8-isoprostane. The açaí powder showed a total polyphenol content of 962.7±22.2 mg EAG/100g, total anthocyanin’s up to 938.5±19.1 mg C3GE/100g, the antioxidant capacity of 643±24.32 µmol TE/100g and 14.07±0.45 g VCE/100g. In the intervention study, no significant differences were observed between before and after the different biochemical markers except for 8-isoprostane, suggesting that the consumption of dehydrated açaí caused effects benefices in the population tested.